Predictors of early stem loosening after total hip arthroplasty: a case-control study. - Melloh, Markus; Eggli, S.; Busato, A.; Roder, C. (2011)
To evaluate the influence of patient characteristics on stem loosening after cemented or uncemented total hip arthroplasty (THA) using a matched case-control study. METHODS; Consecutive records of 4372 cemented (716 cases and 3656 controls) and 809 uncemented (115 cases and 694 controls) primary THAs between 1981 and 2003 in 30 hospitals in 8 European countries were reviewed. Cases and controls were defined as patients with and without stem loosening, respectively. In cases of bilateral THA, patients were their own controls. Cases and controls were matched for hospital, date of surgery, date of follow-up, stem type, and head size. Patient characteristics such as gender, age, weight, height, body mass index (BMI), diagnosis, presence of previous surgery on the affected hip, and walking restrictions according to the Charnley classification were recorded. Male patients were at higher risk of cemented stem loosening (odds ratio [OR], 1.76; 95% confidence interval [CI], 1.4-2.2). Older patients were at lower risk of cemented stem loosening; the odds decreased by 3% per year older (OR, 0.97; 95% CI, 0.96-0.98). Regarding BMI, the odds of cemented stem loosening increased by 3% for each additional unit of BMI over 25 kg/m 2 square (OR, 1.03; 95% CI, 1.004-1.05). Patients in Charnley class B had a lower risk of cemented stem loosening (OR, 0.75; 95% CI, 0.61-0.93). Advanced age, female gender, and Charnley class B (as a proxy measure of reduced walking activity) have a protective effect on survival of cemented stems, whereas a higher BMI was a risk factor.